Diagnosis dan Tatalaksana Terkini Glaukoma - Zahra, Azkiya (Jurnal Klinik dan Riset Kesehatan, 2024)
Glaucoma is one of the leading cause of irreversible blindness in global population. Glaucoma is usually characterized with elevated intraocular pressure (IOP), optic nerve head damage, and decrease of visual field. Continuously high IOP might compress optic nerve head and retinal ganglion cells, causing an irreversible damage. Based on anatomical changes, glaucoma is classified into open angle glaucoma and angle-closure glaucoma. Current management of glaucoma, consisting of pharmachology treatment, laser treatment, and surgery treatment, is focusing to prevent glaucoma progressivity by managing TIO to achieve target range. New management strategies are currently being developed, in an effort to restore vision lost due to glaucoma.